Pengaruh Penerapan Model Pembelajaran Discovery Learning Terhadap Pemahaman Konsep Ipas Siswa Kelas Iv Di Sd Negeri Sukarahayu 01: Pengaruh Penerapan Model Pembelajaran Discovery Learning Terhadap Pemahaman Konsep Ipas Siswa Kelas Iv Di Sd Negeri Sukarahayu 01 - hunaina, najma; Barokah, Awalina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the effect of the Discovery learningmodel on the conceptual understanding of Science and Social Studies (IPAS) among fourthgrade students at SD Negeri Sukarahayu 01. The research used a quasi experimental method with a Nonequivalent Control Group Design. The sample consisted of 23 students in Class IV B (experimental) and 23 students in Class IV A (control). The test instruments included multiple-choice and essay questions, validated (r-count 0.931 > r-table 0.413) and reliable (Cronbach’s Alpha 0.769). The t-test results showed a significant difference in conceptual understanding between the two groups (Sig. 0.000 < 0.05). The experimental group’s post-test average score was 85.50%, while the control group’s was 40.60%. This study concludes that Discovery learninghas a positive and significant effect on improving students’ conceptual understanding of IPAS.